2011
DOI: 10.1210/en.2011-1432
|View full text |Cite
|
Sign up to set email alerts
|

Serum IGF-I Is Not a Reliable Pharmacodynamic Marker of Exogenous Growth Hormone Activity in Mice

Abstract: Serum IGF-I is a well-established pharmacodynamic marker of GH administration in humans and has been used for this purpose in animal studies. However, its general suitability in wild-type laboratory mice has not been demonstrated. Here we show that treatment with recombinant human GH (rhGH) in four different strains of laboratory mice increases body weight, lean body mass, and liver weight but does not increase hepatic expression and release of IGF-I. In contrast and as expected, hypophysectomized rats show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
3
17
1
Order By: Relevance
“…These authors had also observed the persistency of high IGF1 levels at adulthood in that GH-overexpression model (Mt-bGH mice) and concluded animals were already maximally stimulated. More recently, IGF1 has been reported not to be a predictable marker of GH function in mice (Bielohuby, et al 2011), which may account for the lack of correlation we found between basal STAT5 phosphorylation levels and IGF1 induction in adult animals.…”
Section: Discussioncontrasting
confidence: 54%
“…These authors had also observed the persistency of high IGF1 levels at adulthood in that GH-overexpression model (Mt-bGH mice) and concluded animals were already maximally stimulated. More recently, IGF1 has been reported not to be a predictable marker of GH function in mice (Bielohuby, et al 2011), which may account for the lack of correlation we found between basal STAT5 phosphorylation levels and IGF1 induction in adult animals.…”
Section: Discussioncontrasting
confidence: 54%
“…This limited the statistical analysis to a Cox regression and, consequently, the small increase in IGF‐1 as a result of GH injection was not detected as being significant. The response of IGF‐1 to GH injection was poor, although it has previously been noted that IGF‐1 may not be a reliable pharmacodynamic marker of exogenous GH treatment in rodents . The increase in body mass was contributed to by an increase in both liver and kidney mass for GH‐treated hamsters.…”
Section: Discussionmentioning
confidence: 94%
“…Thirdly, some of the effects of GH on the brain are probably mediated by peripheral circulating IGF1 (for review, see Å berg et al (2006)). As circulating IGF1 levels are much more even and regulated by the cumulative effect of GH stimulation over 1-2 days (Bielohuby et al 2011), the pulsatility of GH injections may be partially attenuated. Specifically, it appears that there are two major transport systems of IGF1 across the BBB.…”
Section: Effects Of Gh Administration With Respect To Plasticity and mentioning
confidence: 99%